PENGATURAN BAYI TABUNG DITINJAU DARI ASPEK HUKUM PERDATA DI INDONESIA - Aji Titin Roswitha Nursanthy (Sekolah Tinggi Ilmu Hukum Awang Long, 2017)
Science and technology in the field of medical and health in Indonesia is experiencing a very rapid development, proved to have been able to develop a baby tube program and experienced tremendous success. As the first step of success is the birth of the first baby tube in Indonesia in 1988. Baby tube itself is not yet set in the positive law of Indonesia. There is only about the juridical position of children who are born naturally, and in this case regulated in the Civil Code and Law No. 1 Year 1974. The problem of baby tube itself is a matter of human interest that needs to get legal protection. Therefore, a national legislation should be developed that specifically regulates the implementation of baby tube, on the rights of children born through the baby tube process.